Computational Study of Scission Neutrons in Low-Energy Fission: Stationary and Time-Dependent Approaches (Communications in Computational Physics, 2011)
The emission of scission neutrons from fissioning nuclei is of high practicalinterest. To study this process we have used the sudden approximation and also amore realistic approach that takes into account the scission dynamics. Numerically,this implies the solution of the bi-dimensional Schrödinger equation, both stationaryand time-dependent. To describe axially symmetric extremely deformed nuclearshapes, we have used the Cassini parametrization. The Hamiltonian is discretized byusing finite difference approximations of the derivatives. The main computationalchallenges are the solution of algebraic eigenvalue problems and of linear systemswith large sparse matrices. We have employed appropriate procedures (Arnoldi andbi-conjugate gradients). The numerical solutions have been used to evaluate physicalquantities, like the number of emitted neutrons per scission event, the primary fragments' excitation energy and the distribution of the emission points.